Analisis Proses Permohonan Perwalian atas Anak dari Saudara Kandung: Studi Putusan Nomor 375/PDT.P/2023/PA.SGM - Sarumpaet, Muhammad Idris; Harahap, Yadi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Until now, the process of adopting a child or transferring guardianship of a child is still rarely carried out by most people, especially if the child adopted is the child of a sibling or family member, even though legally the application for guardianship of a child is very important in fulfilling the applicable legal provisions. both in court and outside of court. So this research needs to be carried out in order to find out the process for applying for guardianship over children from siblings by studying Decision Number 375/PDT. P/2003/PA. SGM. This research is qualitative research with a normative juridical type of research, using two approaches, namely the statutory approach and the Conceptual Approach. The results of this research prove that legally the petition submitted by the applicant in Decision Number 375/PDT. P/2003/PA. SGM, has fulfilled the applicable legal provisions regarding guardianship applications in religious courts, and the applicant has also fulfilled the 4 (four) conditions that must be met by a guardian, namely, that he is mature and sensible, can be trusted with the child's welfare and is fair, and is able to carry out his duties as a guardian and also a believer.